2022
DOI: 10.1108/jkm-11-2021-0880
|View full text |Cite
|
Sign up to set email alerts
|

Linking enterprise social media use, trust and knowledge sharing: paradoxical roles of communication transparency and personal blogging

Abstract: Purpose The purpose of this study is to investigate the impact of enterprise social media (ESM) use on two trust dimensions – affect-based trust (ABT) and cognition-based trust (CBT) – as mediators in the relationship between ESM use and knowledge sharing. In the first stage of the proposed model, the authors also consider transparent communication (TC) and personal blogging with colleagues (PBC) during work and non-work hours as moderators that reshape trust levels and subsequently promote knowledge sharing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 101 publications
6
49
0
Order By: Relevance
“…Training courses, positive attitude of the employers, investment in knowledge development, motivation of workers, and transformative leadership were significant drivers to motivate manpower towards PKIM [25]. Lifelong skills, job autonomy, amicable work atmosphere, social and network support, and capacity-building workshops positively contributed towards PKIM practices [18,37,53]. Information literacy expertise, employee training and motivation, inspirational talks, investment in workers, CPD, job autonomy, and psychological ownership were vital trends to inspire people to manage personal knowledge and personal information for personal and sustainable professional development [50].…”
Section: Psychological Ownershipmentioning
confidence: 98%
See 3 more Smart Citations
“…Training courses, positive attitude of the employers, investment in knowledge development, motivation of workers, and transformative leadership were significant drivers to motivate manpower towards PKIM [25]. Lifelong skills, job autonomy, amicable work atmosphere, social and network support, and capacity-building workshops positively contributed towards PKIM practices [18,37,53]. Information literacy expertise, employee training and motivation, inspirational talks, investment in workers, CPD, job autonomy, and psychological ownership were vital trends to inspire people to manage personal knowledge and personal information for personal and sustainable professional development [50].…”
Section: Psychological Ownershipmentioning
confidence: 98%
“…Vark and Reino [16] identified that IT efficacy and PKIM were interconnected and proved fruitful for supporting learning and work output. Masood et al [53] proved that there was a positive association between social media efficacy and PKIM practices. Figure 5 reveals the relationship between IT self-efficacy and PKIM for sustainable lifelong learning and organizational performance.…”
Section: Relationship Between It Efficacy and Pkim Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Due to the advancement of digital technology, social media technologies have changed people's daily life drastically, 5 more and more people are willing to search and share information on virtual platforms. [6][7][8] So, PVC is becoming one of the most important channels to share opinions and information. 9 Especially in China, various social networking sites and "we media" have developed rapidly in recent years.…”
Section: Introductionmentioning
confidence: 99%